Craniofacial disorders in the course of Tourette’s syndrome - a review of the literature - Ratajska, Paulina; Łańczak, Joanna; Komisarek, Oskar (Journal of Education, Health and Sport, 2019)
INTRODUCTION: Tourette's syndrome is a neurological disorder in which the patient presents first symptoms, such as motor and voice tics, in childhood. If the disease significantly impairs proper functioning in society, symptomatic treatment is applied. Antipsychotics, dopaminergic receptor blockers, VMAT2 inhibitors, and non-pharmacological treatment are used, leading to a reduction in the incidence of tics by up to 50%. AIMS: The aim of the work is to present the symptoms of the disease, in particular concerning the craniofacial region and the possibility of implementing any treatment.MATERIALS AND METHODS: All data comes from the analysis of the PubMed database. The paper presents cases in which the structures of the oral cavity, eyes and the brain have been damaged.DESCRIPTION OF THE STATE OF KNOWLEDGE: Treatment with TS must take place on many levels and includes pharmacological and non-pharmacological treatment, therefore, patient care should be interdisciplinary.involving specialists such as psychologists, nutritionists, neurologists, anesthesiologists and dentists. The task of such a team is to diagnose the Tourette syndrome, improve patients quality of life, even by limiting the effects of medications (weight gain) or specialist treatment of damage and discomfort caused by symptoms. Psychological therapy remains the primary one, which is why a qualified team of psychologists and psychotherapists is important. Dentists are an important part of the interdisciplinary team, due to the high frequency of tics covering the oral cavity and the associated consequences. Decisions on treatment should be established jointly, referring to a comprehensive look at individual needs and priorities in patient therapy.SUMMARY: It was found that there is a variety of types and intensity of tics in patients with Tourette's syndrome. The clinical team supervising such a patient should be an interdisciplinary team including dentists, neurologists, psychologists or orthopedics to provide patients with comprehensive and multidirectional treatment.